2021
DOI: 10.1038/s41598-021-93809-1
|View full text |Cite|
|
Sign up to set email alerts
|

DES-Tcell is a knowledgebase for exploring immunology-related literature

Abstract: T-cells are a subtype of white blood cells circulating throughout the body, searching for infected and abnormal cells. They have multifaceted functions that include scanning for and directly killing cells infected with intracellular pathogens, eradicating abnormal cells, orchestrating immune response by activating and helping other immune cells, memorizing encountered pathogens, and providing long-lasting protection upon recurrent infections. However, T-cells are also involved in immune responses that result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Several aspects of the molecular functions of miR-4442 remain unclear. Previous studies have indicated that miR-4442, which targets CD6, may be involved in Grave's disease and Hashimoto's thyroiditis [48] and in the proliferation or apoptosis in small airway epithelial cells exposed to transforming growth factor-β [49]. However, there have been no detailed reports on the regulatory function of miR-4442 and its involvement in cancer; therefore, we consider our findings to be significant.…”
Section: Discussionmentioning
confidence: 59%
“…Several aspects of the molecular functions of miR-4442 remain unclear. Previous studies have indicated that miR-4442, which targets CD6, may be involved in Grave's disease and Hashimoto's thyroiditis [48] and in the proliferation or apoptosis in small airway epithelial cells exposed to transforming growth factor-β [49]. However, there have been no detailed reports on the regulatory function of miR-4442 and its involvement in cancer; therefore, we consider our findings to be significant.…”
Section: Discussionmentioning
confidence: 59%